Refleksi sosial dalam antologi cerpen Kita Susah Tidur sejak Dilahirkan karya Aksan Taqwin Embe - Suganda, Nurkalina Pratiwi; Permadi, Tedi; Harini, Yostiani Noor Asmi (Universitas Mulawarman, 2025)
This study presents the dominant social reflection category that appears in the short story anthology Kita Susah Tidur sejak Dilahirkan by Aksan Taqwin Embe. Twelve stories are delivered in a light and simple manner, and the topics discussed in each story reflect the circumstances that occur in the real world. This study uses a qualitative descriptive method in the form of a literature study with Alan Swingewood's literary sociology approach. The results of the study show that in the short story anthology Kita Susah Tidur sejak Dilahirkan, four dominant categories of social reflection appear, namely land confiscation in the short stories Hari Muram and Bisikan-Bisikan; violence against women in the short stories Selawat Sepasang Lansia, Bisikan-Bisikan, Anjing yang Menggagalkan Pernikahan, and Menjemput Tubuh; fishermen's lean season in the short stories Menyisir Kematian and Anjing yang Menggagalkan Pernikahan, and gender stereotypes in the short story Pengarang yang Bermartabat. These four categories of social reflection are relevant to the real world because they are reinforced by Alan Swingewood's theory of literary sociology, which sees literary works as social documents and formulates the concept that literary works can be seen as social reflections.